SODA MAPS: A Framework for Understanding Caffeinated Sugary Drink Consumption Among Children - Halberg, Sabrina E.; Visek, Amanda J.; Blake, Emily F.; Essel, Kofi D.; Sacheck, Jennifer; Sylvetsky, Allison C. (Frontiers in Nutrition, 2021)
Excess sugary drink (SD) consumption is associated with childhood obesity and development of cardiometabolic disease. In addition to having high added sugar content, many SDs also contain caffeine, which may further encourage excess SD consumption among children. The objective of this study was to develop a conceptual framework of children’s caffeinated SD consumption using group concept mapping, an applied social research multimethodology that collectively harnesses qualitative and quantitative data from participants to generate a visual representation of their ideas and input. Children, 8-14 years old, who reported consuming ≥ 12 ounces of caffeinated SDs (e.g., sodas, sweet teas) per day were recruited throughout Washington, D.C. and invited to participate. Concept mapping included three participant-driven activities: (1) brainstorming (n=51), during which children reported reasons for their SD consumption, from which 58 unique reasons were identified; (2) sorting (n=70), during which children sorted each of the reported reasons into categories and named each category; and (3) rating (n=74), during which children rated the influence of each reason on their own caffeinated SD consumption. Similarity matrices, multidimensional scaling, and hierarchical cluster analysis were used to generate concept maps (hereafter “SODA MAPS”), which display the 58 reasons organized within 8 overarching clusters. Among these 8 clusters, Taste and Feel, Something to Do, and Energy were rated as particularly influential. Child caffeinated SD consumption is encouraged not only by the palatable taste and reported preferences for these beverages (e.g., Taste and Feel), but also by psychological (e.g., Mood and Focus), biological (e.g., Energy), social (e.g., Something to Do) or environmental reasons (e.g., Nothing Better Available). Thus, the SODA MAPS can inform the development of tailored, multi-level SD reduction interventions that incorporate strategies to address important and currently overlooked reasons for caffeinated SD consumption among children.